1999
DOI: 10.1099/13500872-145-1-259
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of chitinase in guinea pig tissues and increases in levels of this enzyme after systemic infection with Aspergillus fumigatus

Abstract: Intravenous infection of guinea pigs with the fungus Aspergillus fumigatus resulted in increased levels of chitinase in serum and tissues of the animals. The molecular properties of the enzyme were demonstrated to be different from those of the fungal chitinase, but also from guinea pig lysozyme and /?-Nacetylhexosaminidase. Bio-Gel P-100 gel filtration showed that in liver, spleen, heart and lung tissue of control animals there were two molecular mass forms present with apparent molecular masses of 35 kDa and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 10 publications
4
29
0
3
Order By: Relevance
“…9B). As expected, due to the much reduced concentration of organ chitinase (15,28,37), the opposite pattern was observed in the infected rat brain.…”
Section: Resultsmentioning
confidence: 59%
“…9B). As expected, due to the much reduced concentration of organ chitinase (15,28,37), the opposite pattern was observed in the infected rat brain.…”
Section: Resultsmentioning
confidence: 59%
“…Physiological and pathophysiological roles of bovine gut chitinase in blood are unknown. As Overdijk et al reported that the blood obtained from guinea pigs infected with Aspergillus fumigatus showed a higher chitinase activity than that of the control [13,14], we assumed that the bovine gut chitinase in the blood might play some defensive role against pathogens rather than act as a digestive enzyme. To test this hypothesis, we here established a semi-quantitative method for the measurement of bovine gut chitinase and investigated its changes with aging, systemic inflammation caused by lipopolysaccharide (LPS) injection, and experimental infection with Theileria sergenti in calves or cows.…”
mentioning
confidence: 99%
“…There are some reports showing the existence of chitinase activities in the sera of the goat, guinea pig, and human [10,[12][13][14]. By use of the present immunoblotting, we also tested the possibility that the antibody against bovine gut chitinase could detect protein bands in the plasma of other animal species (Fig.…”
mentioning
confidence: 99%
“…Increases have been observed in various lysosomal disorders, such as malaria, thalassemia and fungal infections (19)(20)(21)(22)(23). In addition, increased activity has been reported in tissues and plasma of guinea pigs infected by Aspergillus fumigates, and in plasma and urine of a neonate with C. albicans infection (23,24). As increased activities of ChT have been described in neonates with bacterial infections (17), this may suggest that the spectrum of anti-microbial action of ChT extends to bacteria, thus playing a complementary role to lysozyme.…”
Section: Discussionmentioning
confidence: 99%